Case Report : Implementation of Pursed-Lips Breathing Technique on Respiratory Rate and Oxygen Saturation in Chronic Obstructive Pulmonary Disease (COPD) Patients in the Pulmonary Ward of Raden Mattaher Hospital Jambi - Gusmarta, Gusmarta; Oktarina, Yosi (Jurnal Keperawatan Universitas Jambi, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a heterogeneous pulmonary condition caused by abnormalities in the airways that result in persistent airflow obstruction. Patients with COPD often complain of shortness of breath (dyspnea), fatigue, limited physical activity, and coughing with or without sputum production. They may also experience exacerbations that require specific prevention and treatment strategies. Management of COPD symptoms can be carried out through both pharmacological and non-pharmacological approaches. One non-pharmacological intervention that can be provided to COPD patients is the pursed-lips breathing (PLB) technique. This scientific paper was designed using a case report approach. The purpose of this case report is to provide an overview of the implementation of pursed lips breathing technique on respiratory frequency and oxygen saturation of patients with COPD. The subject was one patient diagnosed with COPD, admitted to the Pulmonary Inpatient Ward at Raden Mattaher Regional Hospital in Jambi. An oximeter was used as the measuring instrument to assess oxygen saturation, and a digital timer was used to measure respiratory rate over one minute. Data were analyzed descriptively by observing respiratory rate and oxygen saturation from the first day before PLB was performed until the last day of intervention. Changes in respiratory rate and oxygen saturation were observed, where on the first day, the patient’s RR was 25 breaths per minute, which decreased to 23 breaths per minute, and oxygen saturation increased from 95% to 98% after three days of therapy. Pursed-lips breathing (PLB) therapy was proven effective in increasing oxygen saturation and reducing respiratory rate in COPD patients, although the improvements were also influenced by pharmacological management, including bronchodilators and supplemental oxygen. Keywords: Chronic Obstructive Pulmonary Disease (COPD), Oxygen Saturation, Pursed-Lips Breathing, Respiratory Rate.